Materials for electrical contacts and electrical and electronic components
Patent Information
- Application Number
- JP2025058563
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0008】 本開示によれば、優れた耐摩耗性を有する電気接点用材料および電気電子部品を提供することができる。
Smart Images

Figure 2026165913000001_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to materials for electrical contacts and electrical and electronic components. [Background technology]
[0002] Traditionally, alloy coatings made of Ag and Sn have been used in a variety of fields.
[0003] For example, Patent Document 1 describes a surface-treated metal material for the purpose of effectively suppressing contact resistance and insertion force, comprising a base material, a Ni underlayer formed on the base material, a Ni3Sn4 alloy middle layer formed on the Ni underlayer, and an Ag3Sn alloy upper layer formed on the Ni3Sn4 alloy middle layer, wherein the thickness of each layer is within a predetermined range, the Ag3Sn area ratio of the Ag3Sn alloy upper layer in EDS analysis is 97% or more, and the thickness of the oxide film of the Ag3Sn alloy upper layer is less than 2 nm.
[0004] Incidentally, in recent years, electronic devices have become smaller and have longer lifespans, which has increased the load on coatings. In particular, there is a need to reduce wear on contacts that experience slight friction in connectors and on contacts that operate repeatedly, such as switches. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2019-206730 [Overview of the project] [Problems that the invention aims to solve]
[0006] The purpose of this disclosure is to provide electrical contact materials and electrical / electronic components having excellent wear resistance. [Means for solving the problem]
[0007] [1] A base material made of a conductive material, and a surface coating provided on at least a part of the base material, wherein the surface coating includes a Ni-containing layer containing Ni, and an Ag-Sn-containing layer provided on the Ni-containing layer, containing Ag and Sn, and having a hexagonal close-packed structure, the Young's modulus E of the surface of the surface coating measured by a nanoindenter IT is 20000 mgf / μm 2 or more, the material for electrical contacts. [2] The material for electrical contacts according to the above [1], wherein the thickness of the Ag-Sn-containing layer is 1.0 μm or less. [3] The material for electrical contacts according to the above [1] to [2], wherein the average crystal grain size of the Ag-Sn-containing layer is 1.00 μm or less. [4] An electrical and electronic component using the material for electrical contacts according to any one of the above [1] to [3]. [Effects of the Invention]
[0008] According to the present disclosure, it is possible to provide a material for electrical contacts and an electrical and electronic component having excellent wear resistance. [Brief Description of the Drawings]
[0009] [Figure 1] Figure 1 is a cross-sectional view showing an example of the material for electrical contacts of the embodiment. [Modes for Carrying Out the Invention]
[0010] Hereinafter, the embodiment will be described in detail.
[0011] As a result of intensive repeated research on materials for electrical contacts, the present inventors have found that by controlling the Young's modulus E of the surface of the surface coating including the Ni-containing layer and the Ag-Sn-containing layer having a hexagonal close-packed structure within a predetermined range, adhesive wear during fine sliding of the contact can be suppressed and wear resistance can be improved, and the present disclosure has been completed based on such findings. IT , and the present disclosure has been completed based on such findings.
[0012] The electrical contact material of the embodiment comprises a substrate made of a conductive material and a surface coating provided on at least a portion of the substrate, wherein the surface coating comprises a Ni-containing layer containing Ni and an Ag-Sn-containing layer provided on the Ni-containing layer and containing Ag and Sn and having a hexagonal close-packed structure, and the Young's modulus E of the surface of the surface coating measured by a nanoindenter IT is 20000 mgf / μm 2 That's all.
[0013] Figure 1 is a cross-sectional view showing an example of an electrical contact material according to an embodiment.
[0014] As shown in Figure 1, the electrical contact material 1 of the embodiment comprises a substrate 2 and a surface coating 3.
[0015] The substrate 2 constituting the electrical contact material 1 is made of a conductive material. The substrate 2 is preferably made of a metal or an alloy. The metal is preferably copper, and more preferably pure copper. The alloy is preferably a copper alloy, and more preferably a copper alloy of the Cu-Sn-P, Cu-Zn, Cu-Ni-Si, Cu-Sn-Ni, Cu-Cr-Mg, Cu-Cr-Sn-Zn, or Cu-Ni-Si-Zn-Sn-Mg type.
[0016] The shape of the base 2 is not particularly limited and can be appropriately selected depending on the application of the electrical contact material 1, and is preferably a strip or plate, but may also be a rod or wire.
[0017] From the viewpoint of the electrical contact material 1 having excellent overall conductivity, the conductivity of the substrate 2 is preferably 10% IACS or higher, and more preferably 30% IACS or higher. Conductivity (IACS; International Annealed Copper Standard) can be determined by measuring it in a constant temperature bath controlled at 20°C (±1°C) using the four-terminal method.
[0018] The surface coating 3 constituting the electrical contact material 1 is provided on at least a portion of the substrate 2. Figure 1 shows an example in which the surface coating 3 is provided on the entire surface of one of the main surfaces of the substrate 2. The surface coating 3 comprises a nickel (Ni)-containing layer 31 and an Ag-Sn-containing layer 32 containing silver (Ag) and tin (Sn).
[0019] The Ni-containing layer 31 is provided on the substrate 2. The Ni-containing layer 31 contains Ni as its main component. Here, when a predetermined element is contained as the main component, the proportion of the predetermined element to the total elements contained in the layer is 50 at% or more.
[0020] The Ni-containing layer 31 serves as the underlayer for the alloy layer, the Ag-Sn-containing layer 32. This layer suppresses the decrease in conductivity of the electrical contact material 1 caused by the diffusion of components of the substrate 2, such as Cu, into the Ag-Sn-containing layer 32. It also suppresses the increase in contact resistance of the Ag-Sn-containing layer 32 when the electrical contact material 1 is affected by heat, thereby improving the heat resistance of the electrical contact material 1.
[0021] The Ni-containing layer 31 is preferably composed of a nickel-based material such as metallic nickel or a nickel alloy. The nickel alloy is preferably a Ni-P or Ni-Fe nickel alloy.
[0022] Furthermore, at least a portion of the Ni-containing layer 31 may react with Sn atoms diffused during the process of forming the hexagonal close-packed (HCP) structure of the Ag-Sn-containing layer 32 to form a NiSn-based compound at the interface between the Ni-containing layer 31 and the Ag-Sn-containing layer 32. This layer made of the NiSn-based compound is also included in the Ni-containing layer 31.
[0023] From the viewpoint of fully exhibiting the above-mentioned effects of the Ni-containing layer 31, it is preferable that the thickness of the Ni-containing layer be 0.1 μm or more. Furthermore, from the viewpoint of moldability and material cost, it is preferable that the thickness of the Ni-containing layer be 2.0 μm or less.
[0024] The Ag-Sn-containing layer 32 is provided on the Ni-containing layer 31, and constitutes the outermost layer of the surface coating 3, that is, the outermost layer of the electrical contact material 1.
[0025] The Ag-Sn-containing layer 32 has a hexagonal close-packed structure. Specifically, the Ag-Sn-containing layer 32 is a layer including crystal grains having a hexagonal close-packed structure. Since the Ag-Sn-containing layer 32 has a hexagonal close-packed structure, the surface coating 3 of the electrical contact material 1 can suppress adhesive wear during fine sliding and improve wear resistance.
[0026] In the electrical contact material 1, the Young's modulus E of the surface of the surface coating 3 measured by a nanoindenter IT , that is, the Young's modulus E of the surface of the Ag-Sn-containing layer 32 IT is 20000 mgf / μm 2 or more. As described above, when the Young's modulus E of the surface of the surface coating 3 IT is 20000 mgf / μm 2 or more, the surface coating 3 of the electrical contact material 1 can suppress adhesive wear during fine sliding and improve wear resistance. Further, the above Young's modulus E IT is preferably 30000 mgf / μm 2 or less, more preferably 26000 mgf / μm 2 or less, which can suppress the occurrence of cracks in the Ag-Sn-containing layer 32.
[0027] Further, in the Ag-Sn-containing layer 32, the alloy composed of a hexagonal close-packed structure is a ζ (zeta) phase, and it is known that slip deformation occurs in the {0001} plane. That is, when the <0001> direction orthogonal to the {0001} plane is parallel to the normal line of the surface of the Ag-Sn-containing layer 32, the {0001} plane is parallel to the surface of the Ag-Sn-containing layer 32, so the Ag-Sn-containing layer 32 of the electrical contact material 1 is prone to wear due to fine sliding or the like. Therefore, from the viewpoint of improving the wear resistance of the Ag-Sn-containing layer 32, the proportion of crystal grains having the <0001> direction parallel to the surface normal of the Ag-Sn-containing layer 32 in the Ag-Sn-containing layer 32 is preferably 20% or less, and more preferably 15% or less.
[0028] The crystal structure of the crystal grains contained in the Ag-Sn-containing layer 32 can be obtained from crystal orientation analysis data calculated using analysis software (TSL Corporation, OIM Analysis) from crystal orientation data continuously measured using an EBSD detector attached to a high-resolution scanning electron microscope (JEOL Ltd., JSM-7001FA). "EBSD" stands for Electron Backscatter Diffraction, and is a crystal orientation analysis technique that utilizes backscattered electron Kikuchi line diffraction that occurs when an electron beam is irradiated onto the Ag-Sn-containing layer 32 of the electrical contact material 1 in a scanning electron microscope (SEM). "OIM Analysis" is software for analyzing data measured by EBSD. The measurement is performed on a cross section of the electrical contact material that includes the thickness direction, which has been finished using a cross-section polisher or the like. The measurement area in the cross section is approximately 10 μm × 50 μm, and the measurement is performed with a step size of 0.02 μm. In the measurement of the cross section, if the above field size cannot be obtained depending on the sample size, the average value obtained by measuring in multiple fields may be used.
[0029] Here, using crystal orientation data obtained by the EBSD method, measurement points with a reliability index CI value of 0.1 or higher are selected for analysis, and orientation analysis is performed using the profiles of hexagonal close-packed crystal phases such as magnesium. At this time, only the crystal phases having a hexagonal close-packed structure are extracted, and among them, the direction parallel to the normal direction of the surface of the Ag-Sn-containing layer is selected. <0001> The area percentage occupied by directional crystal grains can be calculated.
[0030] Furthermore, the nanoindentation hardness H of the surface of surface coating 3 IT That is, the nanoindentation hardness H of the surface of the Ag-Sn-containing layer 32 IT is 500 mgf / μm 2 The above is preferable. Nanoindentation hardness H of surface coating 3 IT 500 mgf / μm 2 As a result, the surface coating 3 of the electrical contact material 1 is less prone to abrasion during sliding, improving wear resistance. Furthermore, the nanoindentation hardness H of the surface of the surface coating 3IT However, preferably 1000 mgf / μm 2 More preferably, 700 mgf / μm 2 The following conditions can suppress the occurrence of cracks during sliding, thereby maintaining quality.
[0031] Furthermore, in the Ag-Sn-containing layer 32, it is preferable that the average grain size of the crystal grains having a hexagonal close-packed structure is 1.00 μm or less. When the average grain size of the Ag-Sn-containing layer 32 is 1.00 μm or less, adhesive wear during sliding can be further suppressed, and thus adhesive peeling can be further suppressed. Also, when the average grain size of the Ag-Sn-containing layer 32 is preferably 0.50 μm or more, grain boundary diffusion can be suppressed, thus maintaining corrosion resistance and suppressing discoloration.
[0032] The average grain size of the hexagonal close-packed grains contained in the Ag-Sn-containing layer 32 can be obtained from crystal orientation analysis data calculated using analysis software (TSL Corporation, OIM Analysis) from crystal orientation data continuously measured using an EBSD detector attached to a high-resolution scanning analytical electron microscope (JEOL Ltd., JSM-7001FA) for a cross-section including the thickness direction of the electrical contact material. The measurement is performed on a cross-section including the thickness direction of the electrical contact material, which has been finished using a cross-section polisher or the like. The measurement area in the cross-section is approximately 10 μm × 50 μm, and the measurement is performed with a step size of 0.02 μm. If the above field size cannot be obtained in the cross-sectional measurement due to the sample size, the average value obtained by measuring in multiple fields may be used.
[0033] Here, using the crystal orientation data obtained by the EBSD method, measurement points with a reliability index CI value of 0.1 or higher are selected for analysis, and orientation analysis is performed using the profiles of crystal phases with a hexagonal close-packed structure, such as magnesium. At this time, by extracting only the crystal phases having a hexagonal close-packed structure, drawing line segments parallel to the surface of the Ag-Sn-containing layer, and determining the average length of the line segments overlapping with the crystal grains, which are demarcated by both ends of the crystal grains, the average grain size of the crystal grains having a hexagonal close-packed structure can be determined.
[0034] From the viewpoint of further improving the wear resistance and conductivity of the Ag-Sn-containing layer 32, it is preferable that the thickness of the Ag-Sn-containing layer 32 be 0.2 μm or more. Also, from the viewpoint of material cost, it is preferable that the thickness of the Ag-Sn-containing layer 32 be 1.0 μm or less.
[0035] Furthermore, although the Ag-Sn-containing layer 32 contains Ag and Sn as its main components, it may also contain impurities such as Cu and Ni.
[0036] Because such electrical contact material 1 has excellent wear resistance, it is suitable for use in electrical contacts for electrical and electronic components, particularly in electrical contacts for connectors and switches, and especially in electrical contacts for microswitches.
[0037] Furthermore, since electrical and electronic components made using such electrical contact material 1 are equipped with electrical contacts made using electrical contact material 1, the electrical contacts of the electrical and electronic components have excellent wear resistance.
[0038] Next, a method for manufacturing the electrical contact material 1 of the above embodiment will be described.
[0039] The manufacturing method for the electrical contact material 1 comprises a degreasing step, an activation step, a Ni-containing layer formation step, an Ag coating formation step, a Sn coating formation step, and an alloying treatment step. Of these, the degreasing step and the activation step are optional steps.
[0040] The degreasing step is preferably performed to improve the adhesion between the substrate and the surface coating. Cathode electrolytic degreasing is preferred as the degreasing step. Preferred conditions for cathode electrolytic degreasing are shown below.
[0041] Treatment solution: 60 g / L sodium hydroxide aqueous solution Processing temperature: 60℃ Cathode current density: 2.5A / dm 2 Processing time: 30 seconds
[0042] After the degreasing process, it is preferable to perform an activation process to improve the adhesion between the substrate and the surface coating. Preferred examples of conditions for the activation process are shown below.
[0043] Treatment solution: 100 g / L sulfuric acid aqueous solution Processing temperature: 23℃ Immersion time: 30 seconds
[0044] In the Ni-containing layer formation process, a Ni-containing layer is formed on at least one main surface of the substrate by electroplating. Preferred examples of conditions for the Ni-containing layer formation process are shown below.
[0045] Treatment solution: An aqueous solution containing 400 g / L nickel sulfamate, 30 g / L nickel(II) chloride, and 30 g / L boric acid. Processing temperature: 55℃ Current density: 10A / dm 2 Plating thickness: 0.05 μm to 2.00 μm Processing time: Time adjusted according to the plating thickness
[0046] In the Ag coating formation process, a thin Ag coating with excellent density is formed on the main surface of the substrate, which has a Ni-containing layer, by strike plating. Then, electroplating is performed to a predetermined thickness to complete the formation of the Ag coating.
[0047] The following are preferred examples of conditions for strike plating. Treatment solution: Aqueous solution containing 4 g / L silver(I) cyanide and 80 g / L free potassium cyanide. Processing temperature: 30℃ Current density: 5~10A / dm 2 Processing time: 10 seconds
[0048] The following are preferred examples of conditions for electroplating. Treatment solution: An aqueous solution containing 50 g / L silver(I) cyanide, 10 g / L potassium carbonate, and 90 g / L free potassium cyanide. Processing temperature: 30℃ Current density: 1A / dm 2 Plating thickness: 0.20 μm to 4.40 μm Processing time: Time adjusted according to the plating thickness
[0049] In the Sn coating formation step, a Sn coating is formed on the main surface of the substrate that has a Ni-containing layer. Here, the Ag coating and the Sn coating can be laminated in any order. That is, the Ag coating may be formed first and then the Sn coating, or the Sn coating may be formed first and then the Ag coating. In particular, in order to form a thick Ag-Sn-containing layer, the Ag coating formation step and the Sn coating formation step may be repeated.
[0050] It is preferable to laminate the Ag film and Sn film so that the ratio of the thickness of the Ag film to the thickness of the Sn film is in the range of 5:3 to 7:1. That is, it is preferable that the ratio of the thickness of the Sn film to the total thickness of the Ag film and Sn film be in the range of 0.125 to 0.375. By forming the Ag film and Sn film in such a ratio, it is possible to form crystal grains having a hexagonal close-packed structure in the Ag-Sn containing layer. Preferred examples of conditions for the Sn film formation process are shown below.
[0051] Treatment solution: An aqueous solution containing 40 g / L tin(II) sulfate, 60 g / L sulfuric acid, 40 g / L cresol sulfonic acid, and 2 g / L gelatin. Processing temperature: 23℃ Current density: 2A / dm 2 Plating thickness: 0.10 μm to 1.60 μm Processing time: Time adjusted according to the plating thickness
[0052] In the alloying process, heat treatment is performed in a non-oxidizing atmosphere at a temperature of 570°C to 620°C for a time of 30 to 80 seconds. This alloys the Ag and Sn coatings and causes crystal grains with a hexagonal close-packed structure to grow, forming an Ag-Sn containing layer. Furthermore, by controlling the number of heat treatments and the cooling rate after heat treatment, the Young's modulus E of the surface of the surface coating including the Ag-Sn containing layer can be controlled. IT Nanoindentation hardness HIT Control.
[0053] According to the embodiments described above, the Young's modulus E of the surface of the surface coating comprising a Ni-containing layer and an Ag-Sn-containing layer having a hexagonal close-packed structure IT By controlling this within a predetermined range, the wear resistance of electrical contact materials can be improved.
[0054] Although embodiments have been described above, the present invention is not limited to the embodiments described above, and includes all aspects included in the concepts and claims of this disclosure, and can be modified in various ways within the scope of this disclosure. [Examples]
[0055] Examples and comparative examples will be described next, but this disclosure is not limited to these examples.
[0056] (Examples 1-9, Comparative Examples 1-7) Using a 0.15mm thick C5210 H material as the substrate, a 60g / L sodium hydroxide aqueous solution is placed in the electrolytic cell as a degreasing solution and heated. The substrate is then immersed in the degreasing solution heated to 60°C and connected to the anode of the electrolytic cell, with a current flow rate of 2.5A / dm². 2 Cathode electrolytic degreasing was performed by applying current at the specified current density for 30 seconds. Subsequently, activation treatment was performed by immersing the substrate that had undergone cathode electrolytic degreasing in a 100 g / L sulfuric acid aqueous solution at 23°C for 30 seconds.
[0057] Next, a substrate, which serves as the cathode electrode, is placed in the electroplating cell, and a 20cm x 10cm pure Ni plate, which serves as the anode electrode, is placed opposite the front surface of the cathode electrode. 2L of electroplating solution is then added to the cell, and the electroplating process is performed at a temperature of 55°C and a current of 10A / dm². 2 By applying current at the specified current density, a Ni-containing layer of the thickness shown in Table 1 was formed on one main surface of the substrate by electroplating. The electroplating solution used was an aqueous solution containing 400 g / L of nickel sulfamate, 30 g / L of nickel(II) chloride, and 30 g / L of boric acid, with a nickel concentration of approximately 107 g / L.
[0058] Next, a substrate, which serves as the cathode electrode, is placed in the electrolytic cell, and an insoluble plate measuring 20 cm x 10 cm, which serves as the anode electrode, is placed opposite the front surface of the cathode electrode. 2 liters of strike plating solution are then added to the cell, and the electrolytic cell is operated at a temperature of 30°C with a current of 5-10 A / dm². 2 Strike plating was performed by applying current at a current density of 1 A / dm² for 10 seconds. The strike plating solution used was an aqueous solution containing 4 g / L of silver(I) cyanide and 80 g / L of free potassium cyanide, with a silver concentration of approximately 3 g / L. Next, a substrate serving as the cathode electrode was placed in the electroplating cell, and a silver plate measuring 20 cm x 10 cm serving as the anode electrode was placed opposite the front surface of the cathode electrode. 2 L of electroplating solution was added to the cell, and the electroplating was performed at a temperature of 30°C with a current density of 1 A / dm². 2 By applying current at the specified current density, an Ag film of the thickness shown in Table 1 was formed on the surface of the Ni-containing layer by electroplating. The electroplating solution used was an aqueous solution containing 50 g / L of silver(I) cyanide, 10 g / L of potassium carbonate, and 90 g / L of free potassium cyanide, with a silver concentration of approximately 40 g / L.
[0059] Next, a substrate, which serves as the cathode electrode, is placed in the electroplating cell, and a tin plate measuring 20 cm x 10 cm, which serves as the anode electrode, is placed opposite the front surface of the cathode electrode. 2 liters of electroplating solution are then added to the cell, and the electroplating process is performed at a temperature of 23°C and at 2 A / dm². 2 By applying current at the specified current density, a Sn film of the thickness shown in Table 1 was formed on the surface of the Ag film by electroplating. The electroplating solution used was an aqueous solution containing tin(II) sulfate, with a tin concentration of approximately 22 g / L, containing 40 g / L of tin(II) sulfate, 60 g / L of sulfuric acid, 40 g / L of cresol sulfonic acid, and 2 g / L of gelatin. In Comparative Example 1, no Sn film was formed.
[0060] Next, the materials for electrical contacts shown in Table 1 were obtained by heat treatment at the temperatures and times shown in Table 1, followed by cooling under the conditions shown in Table 1. In Comparative Example 1, no heat treatment or cooling was performed.
[0061] [Measurement and Evaluation] The electrical contact materials obtained in the above examples and comparative examples were subjected to the following measurements and evaluations. The results are shown in Tables 1 and 2.
[0062] [1] Young's modulus E IT Using a nanoindenter, in accordance with ISO 14577, with an indentation depth of 0.25 μm, the Young's modulus E of the surface of the surface coating of the electrical contact material (surface of the Ag-Sn containing layer) was determined. IT We measured it.
[0063] [2] Nanoindentation hardness H IT Using a nanoindenter, in accordance with ISO 14577, and with an indentation depth of 0.25 μm, the nanoindentation hardness H of the surface of the surface coating of the electrical contact material (surface of the Ag-Sn containing layer) was measured. IT We measured it.
[0064] [3] Change in contact resistance An energized sliding test was performed on the surface of the surface coating of an electrical contact material using the UMT TriboLab, a multi-functional tribology evaluation machine (friction and wear tester). The increase in contact resistance after 500 sliding cycles compared to the contact resistance before sliding was judged as follows: ◎ if it was less than 5.0 mΩ, ○ if it was between 5.0 mΩ and 10.0 mΩ, and × if it was 10.0 mΩ or more.
[0065] [4] Change in the coefficient of friction An electrical contact sliding test was conducted on the surface of the surface coating of an electrical contact material using a convex terminal (Ag, contact diameter φ25μm) under the conditions of a load of 1N, a current of 1A, a sliding distance of 50μm, and a speed of 1Hz (one cycle per second). After 1000 sliding cycles, a friction coefficient of less than 0.950μk was marked with ◎, 0.950μk or more and less than 1.000μk was marked with ○, and 1.000μk or more was marked with ×.
[0066] [Table 1]
[0067] [Table 2]
[0068] As shown in Tables 1-2, in Examples 1-9, the Young's modulus E of the surface coating comprising a Ni-containing layer and an Ag-Sn-containing layer having a hexagonal close-packed structure IT By controlling it to a predetermined range, the increase in the contact resistance value after sliding was suppressed, and the value of the friction coefficient after sliding was also reduced. On the other hand, in Comparative Examples 1 to 7, the Young's modulus E of the surface coating comprising a Ni-containing layer and an Ag-Sn-containing layer having a hexagonal close-packed structure IT Because the value was outside the specified range, at least one of the contact resistance value and the friction coefficient value after sliding was large. [Explanation of Symbols]
[0069] 1. Materials for electrical contacts 2 Base 3 Surface coating 31 Ni-containing layer 32 Ag-Sn containing layer
Claims
1. A substrate made of a conductive material, A surface coating provided on at least a portion of the substrate and Equipped with, The aforementioned surface coating is A Ni-containing layer containing Ni, An Ag-Sn-containing layer is provided on the Ni-containing layer and contains Ag and Sn, and has a hexagonal close-packed structure. Equipped with, The Young's modulus E of the surface of the surface coating measured by a nanoindenter IT is 20,000 mg f / μm 2 That concludes the description of materials for electrical contacts.
2. The electrical contact material according to claim 1, wherein the thickness of the Ag-Sn-containing layer is 1.0 μm or less.
3. The electrical contact material according to claim 1, wherein the average crystal grain size of the Ag-Sn-containing layer is 1.00 μm or less.
4. An electrical and electronic component comprising an electrical contact material according to any one of claims 1 to 3.
Citation Information
Patent Citations
Surface-treated metal material, method for manufacturing surface-treated metal material, and electronic components
JP2019206730A